2006
DOI: 10.1128/jvi.00049-06
|View full text |Cite
|
Sign up to set email alerts
|

The Cytoplasmic Tail of the Influenza A Virus M2 Protein Plays a Role in Viral Assembly

Abstract: The viral replication cycle concludes with the assembly of viral components to form progeny virions. For influenza A viruses, the matrix M1 protein and two membrane integral glycoproteins, hemagglutinin and neuraminidase, function cooperatively in this process. Here, we asked whether another membrane protein, the M2 protein, plays a role in virus assembly. The M2 protein, comprising 97 amino acids, possesses the longest cytoplasmic tail (54 residues) of the three transmembrane proteins of influenza A viruses. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
162
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(180 citation statements)
references
References 33 publications
14
162
0
1
Order By: Relevance
“…In particular, virus particles generated by infection with a 28-aa deletion mutant virus contained reduced amounts of packaged genome segments [30]. Iwatsuki-Horimoto et al confirmed these findings and, in addition, demonstrated that virions obtained from M2 tail truncated mutant viruses often displayed a filamentous morphology, whereas wild-type virions were spherical [31]. An interaction of the cytoplasmic tail of M2 with M1 and perhaps the genomic ribonucleoprotein complexes may be essential for proper Influenza A virion formation and budding.…”
supporting
confidence: 68%
“…In particular, virus particles generated by infection with a 28-aa deletion mutant virus contained reduced amounts of packaged genome segments [30]. Iwatsuki-Horimoto et al confirmed these findings and, in addition, demonstrated that virions obtained from M2 tail truncated mutant viruses often displayed a filamentous morphology, whereas wild-type virions were spherical [31]. An interaction of the cytoplasmic tail of M2 with M1 and perhaps the genomic ribonucleoprotein complexes may be essential for proper Influenza A virion formation and budding.…”
supporting
confidence: 68%
“…To this purpose a set of H5N1-PR8 reassortant influenza viruses with M or PB1 segments derived from avian or human strains were generated and investigated regarding replication in embryonated chicken eggs and HA content. We chose this strategy as the viral M1 protein interacts with surface glycoproteins and contributes to virus assembly [22], whereas the cytoplasmic tail of the M2 protein is required for efficient genome packaging [24] and also contributes to virus assembly [35]. The PB1 gene was included as it was inherited in some circumstances from a seasonal WT isolate or the pandemic H1N1-2009 virus to the corresponding vaccine strains during classical reassortment.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of M2 is triggered by low pH in host cell endosomes, resulting in an influx of protons into the virus and acidification that releases the viral RNA into the host cell (2)(3)(4). M2 also helps to package viral RNA (5,6) and regulate pH in the Golgi apparatus of infected cells during viral assembly (7). Two FDA-approved adamantane-based drugs, amantadine and rimantadine (2,8), are potent M2 inhibitors that can neutralize influenza virus in humans and other animals.…”
mentioning
confidence: 99%